Manajemen Pendidikan berbasis Nilai-Nilai Karakter Religius - Ahmad Afghor Fahruddin (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2018)
Religious character education in schools principals and teachers play an important role to improve the quality of students in education of religious character, so that principals have programs or activities related to religious character education. With the existence of an educational system based on religious character values, the school hopes can shape the character of students with Islamic character, in this case students have good morals, do not leave their obligations as Muslims and have a great sense of responsibility. In the strategy of forming character education cannot be separated from a plan. Character education in schools is also closely related to school management or management. The intended management is how character education is planned. The application of education in schools can at least be pursued through four alternative strategies in an integrated manner. First, integrating character education content that has been formulated into all subjects. Second, integrating character education into daily activities at school. Third, integrating character education into programmed or planned activities. Fourth, building cooperative communication between schools with parents of students.